Analisis Efektivitas Kebijakan Pajak Hiburan Berbasis E-Pos Dalam Meningkatkan Penerimaan Pajak Di Masa Pandemi Covid-19 Pada Badan Pendapatan Daerah DKI Jakarta Tahun 2020 - Alina Christyan Seso; Notika Rahmi (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The background of this research is that there are still many difficulties faced by entertainment taxpayers in paying e-POS-based entertainment taxes due to lack of knowledge in using technology so that many taxpayers do not report their taxes, causing a decrease in tax compliance and impacting entertainment tax revenues. This study aims to analyze the effectiveness of the e-POS-based entertainment tax policy, supporting entities, inhibiting entities, and the efforts made in realizing the effectiveness of e-POS-based entertainment tax policies. The results of this study indicate that (1) the e-POS-based entertainment tax policy during the Covid-19 pandemic by the Regional Revenue Agency of DKI Jakarta has been running smoothly; (2) factors that support the effectiveness of the e-POS-based entertainment tax policy are e-POS equipment, free communication networks, and the availability of technicians for equipment maintenance; and (3) the inhibiting factors for the effectiveness of the e-POS-based entertainment tax policy are equipment damage, network disturbances, and lack of knowledge of taxpayers. Suggestions in this study are for the Regional Revenue Agency of DKI Jakarta to (1) increase campaign to taxpayers, (2) increase supervision to minimize interference, and (3) further improve the quality of human resources, especially taxpayer knowledge in the use of technology.